The Pengabdian Mahasiswa untuk Meningkatkan Ekonomi, Sosial, dan Keagamaan di Desa Kalidawir - Indrawati, Dwi Wahyu; Alfiansyah, Yusril Nur; Yuwana, Nurria Peppi; Umaroh, Aprilia Widiya; Syarifah, Maura Zidni Tahta; Fatimah, Nur; Syarifuddin, Faisal Akhmad; Rahmadani, M. Dimas; Listyowahadi, M. Alfandi; Pamungkas, Farid Setyo; Rahayu, Intan Putri; Putri, Nur Baiti Isnaini Agus; Syahroni, Andika Ray; Haqiqi, Ahmad Falihuddin; Pradana, Nico Cahya; Fitriyah, Nisaul; Fajriyah, Ayu Rohmatul (Universitas Serang Raya, 2026)
Community Service Lecture (KKN) is a form of student service that aims to make a real contribution to solving problems in rural communities. Kalidawir Village, Tanggulangin District, Sidoarjo Regency, has great economic and social potential but faces challenges such as limited business management skills, access to technology, and educational facilities. KKNT Group 25 students strive to improve community welfare through various activities that focus on economic, social, and religious development. In addition to focusing on the economy and society, KKNT Group 25 students contribute to the development of Kindergarten (TK) infrastructure in Kalidawir Village. This development supports children's early education by providing adequate facilities, as well as planting Family Medicinal Plants (TOGA) to introduce the benefits of medicinal plants and encourage healthy lifestyles. This effort is in line with increasing health awareness and the use of natural resources. Adequate technology and infrastructure are expected to strengthen community empowerment and improve market access and production efficiency of micro enterprises.